A Review of Recent Advances and Future Directions in the Management of Salinity Stress in Finger Millet - Mbinda, Wilton; Mukami, Asunta (Frontiers in Plant Science, 2021)
Salinity stress is a major environmental impediment affecting the growth and production of crops. Finger millet is an important cereal grown in many arid and semi-arid areas of the world characterized by erratic rainfall and scarcity of good-quality water. Finger millet salinity stress is caused by the accumulation of soluble salts due to irrigation without a proper drainage system, coupled with the underlying rocks having a high salt content, which leads to the salinization of arable land. This problem is projected to be exacerbated by climate change. The use of new and efficient strategies that provide stable salinity tolerance across a wide range of environments can guarantee sustainable production of finger millet in the future. In this review, we analyze the strategies that have been used for salinity stress management in finger millet production and discuss potential future directions toward the development of salt-tolerant finger millet varieties. This review also describes how advanced biotechnological tools are being used to develop salt-tolerant plants. The biotechnological techniques discussed in this review are simple to implement, have design flexibility, low cost, and highly efficient. This information provides insights into enhancing finger millet salinity tolerance and improving production.